2022
DOI: 10.1097/pas.0000000000001880
|View full text |Cite
|
Sign up to set email alerts
|

Primary NTRK-rearranged Spindle Cell Neoplasm of the Lung

Abstract: Three cases of primary NTRK-rearranged spindle cell neoplasm of the lung with resemblance to those described in the somatic soft tissues are presented. The patients are 2 males and 1 female with age at presentation ranging from 31 to 45 years (mean, 36 y). All the 3 tumors were discovered incidentally during physical examinations. None of the patients had any prior history of mesenchymal neoplasms anywhere else. Computed tomography revealed intrapulmonary mass located in the right upper lobe, left upper lobe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The combined usage of pan-TRK and TrkA may help identify low-grade neoplasms with NTRK1 rearrangement. 7 Of 17 cases, 10 co-expressed CD34 and S100 (10/17, 58.8%), including 5 low-grade, 1 intermediategrade and 4 high-grade tumors. Generally, CD34 and S100 were diffusely expressed in low-grade tumors, whereas they were often focally expressed in high-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined usage of pan-TRK and TrkA may help identify low-grade neoplasms with NTRK1 rearrangement. 7 Of 17 cases, 10 co-expressed CD34 and S100 (10/17, 58.8%), including 5 low-grade, 1 intermediategrade and 4 high-grade tumors. Generally, CD34 and S100 were diffusely expressed in low-grade tumors, whereas they were often focally expressed in high-grade tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, occurrence in the visceral organs has also been described, albeit very rare. Reported sites include uterus (especially uterine cervix), 5,6 intrathoracic cavity (lung, pleura, and heart), 7,8 gastrointestinal (GI) tract, 9 prostate, 8 and bone 10 . In addition, its manifestation in adulthood has also been well documented 8, …”
mentioning
confidence: 99%
“…The majority of mesenchymal tumors with NTRK rearrangement occur in the superficial and deep soft tissues of the extremities, trunk, or head and neck. Occasionally, the tumor may also arise in visceral organs, including the gastrointestinal tract, uterine cervix, the central nervous system, and rarely lung 3–7 . The occurrence of NTRK ‐rearranged spindle cell tumor as a primary lesion in the bone is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, the tumor may also arise in visceral organs, including the gastrointestinal tract, uterine cervix, the central nervous system, and rarely lung. [3][4][5][6][7] The occurrence of NTRKrearranged spindle cell tumor as a primary lesion in the bone is extremely rare. According to a recent study that embraced 354 bone tumors, NTRK fusions were not identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation